2011
DOI: 10.1002/ca.21234
|View full text |Cite
|
Sign up to set email alerts
|

A unilateral accessory flexor carpi ulnaris muscle observed during cadaveric dissection

Abstract: Musculature anomalies in the upper limb are common and may result in limb posture deformities or compression neuropathies. In this study, we describe a rare case of accessory flexor carpi ulnaris muscle observed during dissection of the forearm as part of a graduate gross anatomy course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…There are approximately 14 reported cases of Type III FCU anomaly in the anatomy and surgical literature. [2][3][4][5][6][7][8][9][10][11][12][13][14] The embryological basis of the anomaly is thought to be due to the anomalous separation of the flexor blastemal based on the morphology of the reported cases. 4 Based on the previous case reports and proposed embryological hypothesis, there are other potential anomalies associated with the Type III accessory FCU that include an absent PL, duplication of PL and flexor carpi radialis brevis, in addition to variations of the PL such as insertion onto the flexor retinaculum or median nerve innervation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are approximately 14 reported cases of Type III FCU anomaly in the anatomy and surgical literature. [2][3][4][5][6][7][8][9][10][11][12][13][14] The embryological basis of the anomaly is thought to be due to the anomalous separation of the flexor blastemal based on the morphology of the reported cases. 4 Based on the previous case reports and proposed embryological hypothesis, there are other potential anomalies associated with the Type III accessory FCU that include an absent PL, duplication of PL and flexor carpi radialis brevis, in addition to variations of the PL such as insertion onto the flexor retinaculum or median nerve innervation.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a supernumerary muscle belly is rare when compared to descriptions of anomalous insertions or small extra tendinous slips. Furthermore, there are inconsistencies in the literature with regard to the nomenclature of the supernumerary muscles that have included digastric FCU, 3 accessory FCU, 2 and flexor carpi ulnaris palmaris (FCUP). 6 Bhardwaj et al recently described a new classification system for supernumerary FCU in the surgical literature in an attempt to consolidate and clearly classify the anomaly, so as the reporting of their incidence and clinical features could be accurately assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally to nerve compression, an aberrant muscle may be also associated with thrombosis of the ulnar artery (Moss and Forthman, 2008). Anomalies of the flexor carpi ulnaris can also be responsible for flexion deformities (Alvin et al, 2011). Patients can also present with symptoms of median nerve compression due to such aberrant structures, which can be misdiagnosed as resulting from more common causes, such as radiculopathy and carpal tunnel syndrome (Vollala et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies were either about anatomical findings in cadavers or those found incidentally in the operating field [2][3][4][5][6][7][8][9][10][11]. Although the majority of anomalous muscles are asymptomatic, they may occasionally produce persistent pain, unexplained mass, or compression neuropathy necessitating surgical excision [7,8,[11][12][13][14][15][16][17]. Despite several anatomical descriptions, the actual reports of the clinical application of such anomalous muscles are sparse.…”
Section: Introductionmentioning
confidence: 99%